Analisis Produktivitas Kerja Karyawan Bagian Cetak Surat Kabar di Propinsi Riau - Iskandar, Iskandar (Komunitas Manajemen Kompetitif, 2015)
Abstrak: From the calculation results obtained indicate that the F-count is greater than F-table. Thus the hypothesis that incentives, training, work experience, facilities and infrastructure are factors that affect labor productivity in the print media company in the city of Pekanbaru accepted. So based on the results of testing on variable incentives can be seen that the t-test bigger than t-table. It can be concluded that the incentive variables have positive and significant influence. Based on the results of testing on training variables can be seen that t count> t-table. It can be concluded that the partial training variables have a strong relationship affect productivity in the workplace. Based on the test results in a variable work experience can be seen that t count> t-table. It can be concluded that the partial work experience variables have a strong relationship affect productivity in the workplace. Based on test results on the variable infrastructure can be seen that t count> t-table. It can be concluded that the variable infrastructure partially have strong relationships in influencing labor productivity at print media company in the city of Pekanbaru. Keywords: Employee Productivity